Peradilan Adat Badamai Kewarisan Islam Banjar Perspektif Madrasah Ahlul Hadis Dan Madrasah Ahlurra’yi - Jaidi, Muhammad; Jalaluddin, Jalaluddin; Azhari, Fathurahman; Hamdi, Fahmi (Interdisciplinary Explorations in Research Journal, 2024)
Abstrack The customary court of Badamai is a significant cultural heritage preserved in various regions of Indonesia, reflecting local wisdom in resolving disputes and upholding justice. Among the Banjar community in South Kalimantan, Badamai is a deeply rooted form of dispute resolution that prioritizes deliberation and consensus. This practice not only reflects the social values of the Banjar community but also demonstrates the flexibility of Islamic law in adapting to local contexts. This study aims to explore the application of Islamic inheritance law within the framework of the Badamai customary court from the perspectives of the Madrasah Ahlul Hadis and the Madrasah Ahlurra’yi. By examining how these two schools of thought interpret and apply Islamic inheritance laws, the research provides a comprehensive understanding of the interaction between Islamic jurisprudence and local traditions. The findings highlight the adaptability of Islamic law in accommodating local customs, contributing to the broader discourse on the integration of Islamic principles with indigenous practices. This exploration offers valuable insights into the dynamic relationship between religious jurisprudence and cultural heritage, emphasizing the importance of contextualizing Islamic law within the unique socio-cultural landscape of the Banjar community. Keywords: Customary Court, Badamai, Banjar Community, Islamic Inheritance Law, Madrasah Ahlul Hadis, Madrasah Ahlurra’yi Abstrak Peradilan adat Badamai merupakan salah satu warisan budaya yang masih dilestarikan di berbagai daerah di Indonesia, mencerminkan kearifan lokal dalam menyelesaikan perselisihan dan menegakkan keadilan. Di kalangan masyarakat Banjar di Kalimantan Selatan, Badamai adalah bentuk penyelesaian sengketa yang kuat mengakar yang mengutamakan musyawarah dan mufakat. Praktik ini tidak hanya mencerminkan nilai-nilai sosial masyarakat Banjar tetapi juga menunjukkan fleksibilitas hukum Islam dalam beradaptasi dengan konteks lokal. Studi ini bertujuan untuk mengeksplorasi penerapan hukum kewarisan Islam dalam kerangka peradilan adat Badamai dari perspektif Madrasah Ahlul Hadis dan Madrasah Ahlurra’yi. Dengan meneliti bagaimana kedua aliran pemikiran ini menafsirkan dan menerapkan hukum kewarisan Islam, penelitian ini memberikan pemahaman komprehensif tentang interaksi antara yurisprudensi Islam dan tradisi lokal. Temuan ini menyoroti kemampuan adaptasi hukum Islam dalam mengakomodasi adat setempat, berkontribusi pada diskursus yang lebih luas tentang integrasi prinsip-prinsip Islam dengan praktik-praktik adat. Eksplorasi ini menawarkan wawasan berharga tentang hubungan dinamis antara yurisprudensi agama dan warisan budaya, menekankan pentingnya mengontekstualisasikan hukum Islam dalam lanskap sosio-kultural unik masyarakat Banjar. Kata Kunci: Peradilan Adat, Badamai, Masyarakat Banjar, Hukum Kewarisan Islam, Madrasah Ahlul Hadis, Madrasah Ahlurra’yi